7
$\begingroup$

Suppose we have a homomorphism $\alpha, \beta, \gamma$ of short exact sequences: $$ \begin{matrix} 0 & \to & A & \xrightarrow{\psi} & B & \xrightarrow{\phi} & C & \to & 0 \\ \ & \ & \downarrow^{\alpha} & \ & \downarrow^{\beta} \ & \ & \downarrow^{\gamma} \\ 0 & \to & A' & \xrightarrow{\psi'} & B' & \xrightarrow{\phi'} & C' & \to & 0 \end{matrix} $$

If both $\alpha, \gamma$ are surjective then so is $\beta$. This can be proved using the properties of the diagram somehow.

I've tried several things.

$\endgroup$
2
$\begingroup$

It should be straightforward.

We want to prove $\beta$ is surjective, so start out from an arbitrary element $b'\in B'$. We can do one thing: consider $c':=\phi'(b')\in C'$.
Since $\gamma$ is surjective, we get $c$ with $\gamma(c)=c'$.

That the pair $\phi,0$ of maps is exact means nothing else but that $\phi$ is surjective. It yields an element $b\in B$, such that $\gamma\phi(b)=c'=\phi'(b')$.

Now we might not get $\beta(b)=b'$ with this element $b$, nevertheless, we have that $\beta(b)$ and $b'$ has the same image under $\phi'$, so by exactness, this gives $a'\in A'$ such that $\psi'(a')=b' - \beta(b)$.

Can you take it on from here?

$\endgroup$
2
$\begingroup$

Thanks to Berci and Pedro Tamaroff.

Let $b' \in B'$. Then $\phi'(b') = c' \in C'$ and by surjectivity of $\gamma$, there's $c \in C$ with $\gamma(c) = \phi'(b')$ and there's $b \in B$ with $\phi(b) = c$. So $\gamma\phi(b) = \phi'(b') = \phi'(\beta(b))$. So $\beta(b) - b' \in \ker \phi' = \psi'(A') = \psi' \alpha(A)$. So there's $a \in A$ so that $\psi'\alpha(a) = \beta(b) - b' = \beta \psi(a)$. Then clearly $b'$ can be written as the image of the element $b - \psi(a)$ under $\beta$. We're done.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.